Fostering Heroism in Fourth- and Fifth-Grade Students. (July 2019) - Heiner, Elisabeth K.
This study empirically evaluated the potential effect of a training program created by The Hero Construction Company designed to foster heroism in children. The presentation was geared toward encouraging young children to think about taking action when faced with moral dilemmas. The intention of the material is to encourage heroic acts and prosocial behavior. Student participants learn about heroism, and are asked to imagine themselves behaving heroically, and to think about who their heroes are and why. The curriculum asks students to consider their reactions to morally complex situations, and seeks to empower them with the idea that they are "heroes in waiting, " and can stand up to injustices they may witness, such as bullying. Hypotheses were developed to evaluate the potential effect The Hero Construction Company's presentation has on courage levels in children who participate in the training. The study sought to answer the primary question: Can heroism be learned, remembered, and then utilized over the child's lifetime? Sixty-two fourth- and fifth-grade students in Michigan attended the Hero Construction Company's presentation. They were administered the Courage Measure for Children (CM-C) immediately prior to the presentation (Time 1), immediately following (Time 2), and 30 days following (Time 3). The researcher hypothesized that the students' self-reported levels of courage would increase between prepresentation and postpresentation, and prepresentation and 30 days postpresentation. Results indicated a significant increase in the children's courage levels for both time points.